Edukasi Penggunaan Moda Transportasi yang Aman Bagi Pelajar SMK Purnama 01 Semarang - Yesina Intan Pratiwi; Wardana Galih Pamungkas; Son Haji (Jurnal Pengabdian KOLABORATIF, 2025)
This community service activity aims to educate students of SMK Purnama 01 Semarang about safe transportation options, focusing on reducing the risk of traffic accidents involving students. The main issue is the high number of accidents involving students using private vehicles and their limited understanding of traffic safety. The objective of this activity is to raise students' awareness of the importance of choosing safe transportation modes and applying the principles of "safety riding." The methodology employed includes field surveys, discussions with activity partners, and training on driving safety. This training covers the use of personal protective equipment and understanding traffic regulations. As a result, the activity led to an increase in students' knowledge of traffic safety, particularly regarding the use of helmets and seat belts, as well as the application of safe driving principles. Additionally, the activity raised students' awareness of accident risks and how to respond to them. The enthusiasm of the students in participating in the training and discussions indicates that this educational approach is effective in enhancing their understanding. In conclusion, this service has positively impacted the transportation safety of SMK Purnama 01 Semarang students and highlights the importance of integrating transportation safety education into the school curriculum to ensure safer travel for students on the road.